2007
DOI: 10.1115/1.2748473
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thread and Bearing Friction Coefficients on the Vibration-Induced Loosening of Threaded Fasteners

Abstract: This study provides a theoretical and experimental investigation of the effect of the thread and bearing friction coefficients on the self-loosening of threaded fasteners that are subjected to cyclic transverse loads. The friction coefficients are varied by using different types of coating and lubrication. A phosphate and oil coating and an olefin and molydisulfide solid film lubricant are used on the bolts tested. A mathematical model is developed to evaluate the self-loosening behavior in threaded fasteners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…The main failure mode for bolted joint when exposed to vibrational environment is self-loosening Housari et al [32] Effect of thread and bearing friction coefficients on the vibration-induced loosening of threaded fasteners…”
Section: Screw Self-loosening In Bolted Jointsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main failure mode for bolted joint when exposed to vibrational environment is self-loosening Housari et al [32] Effect of thread and bearing friction coefficients on the vibration-induced loosening of threaded fasteners…”
Section: Screw Self-loosening In Bolted Jointsmentioning
confidence: 99%
“…The varying axial load can cause micro slippage between the contact thread [31]. Housari et al [32] concluded that the friction coefficient that plays a role in the loosening rate is affected by the fastener coating and lubricant.…”
Section: Ricci Et Al [35]mentioning
confidence: 99%
“…They found that the increase of the friction coefficient decreased the preload loss. Houari [18] and Karamis [27] showed that the increase of the bearing friction reduced the loosening rate. Furthermore, Zaki et al [19] found that the increase of the coating thickness decreased the friction coefficients of the thread and head bearing, therefore thick coated fasteners would loosen at a faster rate than thin coated fasteners [28].…”
Section: Introductionmentioning
confidence: 99%
“…There has been much research on this topic. Self-loosening mechanisms [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and their various influencing factors [17][18][19][20][21] were studied through experiments, theoretical analyses and numerical simulation. A variety of measures were proposed to prevent self-loosening, such as chemical locking [21], step lock bolt (SLB) [22], and double-nut [8,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation